Pengaruh Gaya Kepemimpinan Transformasional terhadap Keterlibatan Kerja Dimediasi Kepuasan Kerja - Fullchis Nurtjahjani; Ridolof Wenand Batilmurik; Masreviastuti Masreviastuti (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2020)
The aim of this research was to analyze the effect of transformational leadership on work engagement is mediated by job satisfaction. The type of research is positivist reasearh. The analytical method used is Partial Least Square Smart Program (PLS) Version 2.0 PLS based on the Variance Based Structural Equation Modeling (SEM) approach. This research was conducted at State Polytechnic of Malang. The population of this study uses a census (saturated sample, so that the number of samples is the same as the number of the population. The results show that transformational leadership has no significant effect on work engagement and job satisfaction mediate the effect of transformational leadership on work engagement.